Epidemiologic study of in-hospital cardiopulmonary resuscitation among pediatric patients: A retrospective, population-based cohort study in South Korea. Issue 36 (9th September 2022) - Oh, Tak Kyu; Choi, Chang Won; Song, In-Ae
Abstract : We aimed to examine the clinical trends of in-hospital cardiopulmonary resuscitation (ICPR) and factors associated with live discharge following ICPR. As a national population-based cohort study, data were extracted from the South Korean National Inpatient Database. This study included 8992 pediatric patients under 18 years of age who underwent ICPR due to in-hospital cardiac arrest during hospitalization in South Korea between 2010 and 2019 (10 years). The annual prevalence, survival, duration of hospitalization, and total cost of hospitalization at ICPR were examined as clinical trends. In 2010, 7.94 per 100, 000 pediatric patients received ICPR; the prevalence increased to 11.51 per 100, 000 pediatric patients in 2019. The 10-year survival rates were similar, and the in-hospital, 6-month, and 1-year survival rates over 10 years were 44.0%, 34.0%, and 32.4%, respectively. The mean length of hospital stay at ICPR in 2010 was 20.7 (95% confidence interval [CI]: 19.3–22.2) days; this decreased to 16.6 (95% CI: 15.2–18.0) days in 2019. The mean total cost at ICPR was 11, 081.1 (95% CI: 10, 216.2–11, 946.1) United States Dollars (USD) in 2010; this increased to 22, 629.4 (95% CI: 20, 588.3–24, 670.5) USD in 2019. The prevalence of ICPR increased among pediatric patients in South Korea between 2010 and 2019; however, the survival rates were similar for the 10 years. The length of hospital stay at ICPR gradually decreased from 2010 through 2019, while the total cost of hospitalization at ICPR has gradually increased between 2010 and 2019.